Case Study of Biopro (M) Sdn. Bhd. the Strategic Management Plan - Chew, Yoke Mol (1999)
This is a case study report on Biopro (M) Sdn. Bhd. - a latex disposable glove manufacturing company which is experiencing loss in revenue due to global steep slide in the price of latex disposable glove. The company is facing intense pressure from existing customers to match the current market price. The problem is aggravated by the inefficiency in the company' s operations such as malfunctioning of machine, high reject rate, increase in labor cost which have further increased the cost of production. In the effort to revive the company' s competitive positioning in the global market, management by objectives (MBO) has been recommended. This includes the following steps: establish functional objectives, formulate action plans, implement plans and maintaining controls.